Struktura konsumpcji gospodarstw domowych w Polsce na tle wzorców europejskich - Starzyńska, Wacława; Dobrowolska, Bogusława (The Structure of Households' Consumption in Poland on Background of the European Models, 2008)
It is widely accepted that one of the measures of the evaluation of market functioning is the structure of consumer's expenditures of households. The structure of expenditures and its orientation towards purchasing specific goods' categories enable to perceive similarities and differences between standards of living of populations of various countries. The general economic development of Poland caused the increase in aspirations and development of consumer needs of the Polish people. The evaluation of the condition and rate of changes in Polish structures of consumption undoubtedly requires determining a certain point of reference. It seems that it should be the developed European Union countries, which are presently becoming the source of information and aspiration for the Polish people, nearly in all aspects of life. The paper aims at attempting to evaluate the changes of Polish households, as well as to indicate similar structures of consumption of some countries of the European Union by means of Czekanowski’s diagram. In order to analyze the problem we used published materials of the Central Statistical Office, Eurostat and other statistical sources. However, it is necessary to emphasize that both countries 'selection and the period in which the investigation was conducted depended on available sources of information. It turns out though that the direction of changes in Polish structures of consumption is compatible with the known tendencies of the evolution of consumption influenced by the income increase, visible in all economically developed countries of the world. However, the Polish structures of consumption differ greatly from the structures of consumption of many European countries, especially those of a higher economical development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 518-527